Inter-Eye Comparison in Highly Myopic Patients with Unilateral Myopic Traction Maculopathy. (3rd April 2022) - Tian, Jiaxin; Qi, Yue; Zhang, Yinghan; Lin, Caixia; Wang, Ningli
ABSTRACT: Purpose: To evaluate the risk factors for myopic traction maculopathy (MTM) through inter-eye comparisons of asymmetric ocular features in patients with unilateral MTM. Materials and Method: Highly myopic patients with unilateral MTM were enrolled in the study. The results of comprehensive ophthalmologic examinations, color fundus images, and optical coherence tomography (OCT) were reviewed. MTM and myopic atrophic maculopathy was evaluated according to the ATN classification system. The status of the posterior vitreous detachment (PVD), posterior precortical vitreous pocket, vitreoretinal interface abnormalities, posterior staphyloma height (PSH), and the location of the protrusion of the sclera were assessed through OCT. Results: Among the 54 eyes of 27 patients 48.89 ± 12.78 years of age, the affected eyes had worse best-corrected visual acuity, a longer axial length (AXL), greater PSH, and higher rates of posterior staphylomas, vitreovascular traction and epiretinal membranes (ERMs) than the fellow eyes ( P < .001; P < .001; P < .001; P = .010; P = .002; P < .001). Thirteen cases present obvious anisometropia with an inter-eye AXL difference of more than 1 mm. In the 14 cases without obvious anisometropia, the eyes with MTM still had longer AXL, greater PSH and a higher ERMs rate than the fellow eyes ( P = .039; P = .017; P = .001). Besides, in the 7 cases with an inter-eye AXL difference of less than 1 mm and asymmetrical stages of PVD, 5 cases with greater PVD in the affected eyes. Multiple risk factors coexisted in 96% of cases. Conclusions: In patients with unilateral MTM, a longer AXL, greater PSH, posterior staphyloma, vitreovascular traction, and ERMs were the main factors contributing to the occurrence of MTM. The process of PVD might involve in MTM development.